MODEL DISKRIMINASI UPAH PROFESI AUDITOR DI INDONESIA - Rina Trisnawati (Universitas Muhammadiyah Semarang, 2011)
Previous studies by Trisnawati et al ( 2005, 2006, 2007, 2008, 2010) show the existence of wagedifferentials between male and female auditors. In most cases, female auditors receive lower wage as comparedto male auditors. Analysis used is basic model wages discrimination ( Oaxaca-wages decomposition model).Continously, basic model had been using widely with another decomposition techniques. They are Oaxaca 1,Oaxaca 2, Reimers, Cotton dan Neumark models (Trisnawati et al., 2007,2008, 2010) and the results showedconsistently that discrimination is most important factor which cause wages differentials between female andmale auditors. They have consistent results with auditor profession ini England (Rhoda, 1998) Australia(Wilson, 2003), New Zealand (Helewa , 2005), and Canada (Flo Hamrick, 2007).The most weakness from OAXACA wages decomposition model had been using by Trisnawati et al.(2005, 2006, 2007, 2008, 2010), is determining the discrimination coefficient from unexplained variable. Theresidual value has to compute separately from the discrimination value. So, it should be done comprehensivemethod to heal the weakness of decomposition model. The model will use quantile regression with combinationby bootstrap technique. This model done by Mochado and Matta (2007), Melly (2008) by computing wagesdiscrimination among private and public employee in Germany.The main objectives of this study are to identifythe factors that determine gender wage level and gender wage differentials among auditors profession andexamine the existence of discrimination by quantile regression method with bootstrap technique